De la Escuela de Barbizon a van Gogh - Glusberg, Jorge; O'Donnell, Mario; Razelli, G.B. (Buenos Aires : MNBA - Museo Nacional de Bellas Artes Buenos Aires, 1996)
Aublet, Albert ; Barye, Antoine-Louis ; Besnard, Paul-Albert ; Bonheur, Rosa ; Bonnat, Léon-Joseph ; Bonvin, François ; Boudin, Eugène-Louis ; Brispot, Henri ; Cézanne, Paul ; Charlet, Nicolas Toussaint ; Ciceri, Eugène ; Corot, Jean-Baptiste Camille ; Courbet, Gustave ; Daubigny, Charles-François ; Daumier, Honoré ; Degas, Edgar ; Diaz de la Pena, Narcisse-Virgile ; Dupré, Jules ; Fantin-Latour, Henri ; Forain, Jean-Louis ; Français, François-Louis ; Gauguin, Paul ; Gavarni, Paul ; van Gogh, Vincent ; Guillaumin, Jean-Baptiste-Armand ; Harpignies, Henri-Joseph ; Jacque, Charles-Emile ; Jongkind, Johann-Barthold ; L'Hermitte, Léon-Augustin ; Lebasque, Henri ; Lebourg, Albert ; Manet, Edouard ; Menard, Marie-Auguste-Emile-René ; Millet, Jean-François ; Monet, Claude ; Monticelli, Adolphe ; Morisot, Berthe ; Pissarro, Camille ; Puvis de Chavannes, Pierre ; Raffaëlli, Jean-François ; Redon, Odilon ; Renoir, Pierre-Auguste ; Ribot, Théodule-Augustin ; Richer, Léon ; Rodin, Auguste ; Rops, Félicien ; Rousseau, Philippe ; Rousseau, Théodore ; Sisley, Alfred ; Steinlen, Théophile-Alexandre ; de Toulouse-Lautrec, Henri ; Trouillebert, Paul-Désiré ; Vollon, Antoine ; Whistler, James Abbott McNeill ; Ziem, Félix
biografie
Spaans
boek